Aleurites moluccanus (l.) Willd. Extracts Inhibit the Growth of Bac- terial Triggers of Selected Autoimmune Inflammatory Diseases - Mpala, Lindiwe Nomathemba; Chikowe, Getmore Rumbudzai; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Aleurites moluccanus (L.) Willd. is a large tree with a wide global distribution. All parts of the tree have been used medicinally and the nut is consumed in a variety of cuisines. Despite this, A. moluccanus nut extracts have not been rigorously examined growth inhibitory proper- ties against many bacteria, including the bacterial triggers of autoimmune inflammatory diseases. Methods: The antimicrobial activity of A. molucca- nus nut solvent extractions was investigated by disc diffusion and growth time course assays against a panel of bacterial triggers of autoimmune diseases. The growth inhibitory activity was further quantified by MIC de- termination. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: Methanolic and aqueous A. moluccanus nut solvent ex- tracts were potent inhibitors of all of the bacterial triggers of autoimmune diseases screened in this study. The methanolic extract displayed the most potent bacterial growth inhibitory activity. It was particularly potent against the bacterial triggers of rheumatoid arthritis (MICs of 438 and 215 µg/mL against reference and clinical Proteus mirabilis strains; MIC of 187 µg/mL against Proteus vulgaris). The methanolic extract was also a good inhibi- tor of K. pneumoniae and S. pyogenes growth with MICs < 1000 µg/mL. The aqueous and ethyl acetate extracts were also potent bacterial growth inhibitors, albeit with slightly higher MIC values. The antibacterial activity of the methanolic and aqueous A. moluccanus nut extracts were further in- vestigated by growth time course assays which showed significant growth inhibition in cultures of P. mirabilis, K. pneumpniae and S. pyogenes within 1 h of exposure. All extracts were determined to be nontoxic in the Artemia franciscana nauplii bioassay, indicating their safety for prophylactic use in preventing these autoimmune inflammatory diseases. Conclusions: The lack of toxicity of the A. moluccanus nut extracts and their growth inhibi- tory bioactivity against the bacterial triggers of rheumatoid arthritis, anky- losing spondylitis and rheumatic heart disease indicate their potential in the development of new therapies targeting the onset of these diseases.
Keywords: Euphorbiaceae; Candlenut; Rheumatoid Arthritis; Ankylosing Spondylitis; Rheumatic Heart Disease; Antibacterial Activity; Medicinal Plants.